The Faces of the Second Amendment Outside the Home, Take Two: How We Got Here and Why it Matters - Charles, Patrick J. (2016)
Since the late twentieth century, the Second Amendment has been increasingly promoted as the unfettered right to carry firearms in the public concourse. This expansive meaning, however, lacks historical support. Historical evidence reveals a disparity between the Anglo-American origins of armed carriage laws and present-day interpretations of the Second Amendment. The historical backdrop also reveals the impact pro-gun organizations have had on the expansion of armed carriage. Differences in state armed carriage laws, analyzed from both historical and regional perspectives, will one day require the Supreme Court to determine which version of history should dictate the meaning of the Second Amendment